Physiological demands of water polo goalkeeping - Platanou, T. (Journal of Science and Medicine in Sport, 2009)
The purpose of this study was to investigate the physiological demands of water polo goalkeepers during competition and to examine whether the playing intensity of the goalkeeper decreases as the game time progresses. During eight official games the following measurements were performed on eight elite water polo goalkeepers: (1) video analysis of activities, (2) monitoring of blood lactate (BLa) and (3) continuous recording of heart rate (HR) responses. Mean HR of total mixed playing time, excluding breaks among quarters, was 134.3 ± 20.3 bpm for 36 (4 × 9) min of game duration. The large portion of the game (85.6%) was performed with a HR lower than 151.4 ± 2.7 bpm (82.1 ± 1.4% of HRpeak) an intensity corresponding to the players` anaerobic threshold (3.49 ± 0.60 mmol L-1). However, an important part of the game (14.4%) contained activities with sudden HR increases above the anaerobic threshold. Mean BLa accumulation at the end of each game period was 3.93 ± 1.64 mmol L-1. Individual lactate values varied from 2.0 to 8.3 mmol L-1. Goalkeeper exercise intensity reached its peak value (152.5 ± 10.1 bpm) whenever his team competed with one player less due to player exclusion. No significant differences were found in HR, BLa and the percentage of time spent in each of the activity categories between game periods. In conclusion, goalkeeper's game can be described as of intermittent nature with great variability in the intensity performed. The greater part of the game is associated with a low aerobic demand while an important part of the game contains activities with sudden HR increases above the anaerobic threshold implying also a considerable demand on anaerobic metabolism. The intensity of exercise of the goalkeeper does not differ from period to period.